-6a-36=-4(3a+3)

Simple and best practice solution for -6a-36=-4(3a+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6a-36=-4(3a+3) equation:


-6a-36=-4(3a+3)

We simplify the equation to the form, which is simple to understand
-6a-36=-4(3a+3)

Reorder the terms in parentheses
-6a-36=+(-12a-12)

Remove unnecessary parentheses
-6a-36=-12a-12

We move all terms containing a to the left and all other terms to the right.
-6a+12a=-12+36

We simplify left and right side of the equation.
+6a=+24

We divide both sides of the equation by 6 to get a.
a=4

See similar equations:

| 3x+129= | | -7y=-21+28 | | 1/2(x-5)=x-2 | | 4x+3/-5x-3=-1/2 | | 6v-5+5=6v | | (2x^2+6x-7)+(4x^2+2x+17)-(6x^2-11)= | | -4(4-7b)-3(4b-6)=-30 | | 6(x-2)-2x=-40 | | -147=-7(3-3r) | | A=3X(-1) | | 1+5m+7=-7 | | t*-1.5=8 | | -4*-1.5=6 | | -8(p-5)=109.6 | | 4-3x=4(3-x)-3x | | -0.1875*8=-1.5 | | (x^2+5x+5)-(5x^2-8x+7)= | | 8*t=-1.5 | | -4.45-2=-5.5s-4.2 | | -7k-5(-7k+7)=-3+4(7-8k) | | 6*t=-9 | | 6*(-9)=t | | -(h+7)=-8 | | 12-4n=-(n+1)-5 | | (12y+14)+(-2y-3)= | | x/3+18=44 | | 10+x+5x=7x+2 | | 2x+33-5x=3-7x+2 | | (9x-1)-(4x+3)= | | 31=7(-5n-7)-4(2-6n) | | 3x^2-6x-(2-k)=0 | | .03y+.09(50000-y)=2490 |

Equations solver categories